Educational Philosophy of Sri Ramakrishna : Insights from the Kathamrita/ শ্রী রামকৃষ্ণের শিক্ষাদর্শন : ‘কথামৃত’ থেকে অন্তর্দৃষ্টি (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Sri Ramakrishna Paramahamsa (1836–1886), one of the most influential spiritual teachers of nineteenth-century Bengal, occupies a unique position in the history of Indian thought. His teachings, preserved in Mahendranath Gupta’s Śrīśrī Rāmakṛṣṇa Kathāmṛta (1883–1897), transcend narrow sectarianism and offer a holistic approach to life, ethics, devotion, and education. While not a conventional educationist, his philosophy embodies a pedagogy rooted in simplicity, direct experience, and universal acceptance of truth. His educational thought was not institutional but spiritual, moral, and human-centered, laying the foundation for character-building and value-oriented learning.              This essay seeks to explore the educational philosophy of Sri Ramakrishna with special reference to the Kathamrita. It will analyze his views on the purpose of education, moral development, devotion, social service, and religious tolerance. Furthermore, it will show how his method of teaching—through parables, analogies, and experiential wisdom—provides a model for meaningful pedagogy in contemporary times.
Keywords: Sri Ramakrishna; Kathamrita; education; devotion; morality; tolerance; pedagogy; Renaissance